Answer :

absor201

Answer:

An equation which has the same solution as the given equation is:

( x - 18 ) ( x + 2 ) + 48 = 0 ....

Step-by-step explanation:

The given expression is:

x2-16x+12

Break the constant term:

x^2-16x-36 +48=0

[x^2-16x-36] +48=0

Now break the middle term inside the brackets

(x^2-18x+2x-36)+48=0

Take the common

[x(x-18) +2(x-18)]+48=0

(x-18)(x+2)+48=0

Thus an equation which has the same solution as the given equation is:

( x - 18 ) ( x + 2 ) + 48 = 0 ....

Other Questions